Insurgent truth Chelsea Manning and the politics of outsider truth-telling - Maxwell, Lida (Oxford University Press, 2019)
"This book is about Chelsea Manning's leaking of government documents. Manning told the truth about war and a social order sustained by it. Her truth-telling also revealed the complicity of public and private in casting her - a non-gender-conforming individual - as an improper truth-teller. And Manning's truth-telling unsettled hierarchies of truth-telling that prop up a discriminatory and often oppressive social order. I read Manning not as an isolated political actor, but instead as an outsider truth-teller within a cohort of outsider truth-tellers (such as Virginia Woolf, Bayard Rustin, Audre Lorde), whose practices are distinct yet connected, and whose significance becomes more apparent when read in conjunction with each other"--
Keywords: Manning, Chelsea / 1987-; Woolf, Virginia / 1882-1941; Rustin, Bayard / 1912-1987; Lorde, Audre; Manning, Chelsea -- 1987-; WikiLeaks (Organization); Official secrets / United States; Leaks (Disclosure of information) / United States; Truth / Political aspects; Transgender women / United States / Biography; POLITICAL SCIENCE / History & Theory; POLITICAL SCIENCE / Government / Comparative; PHILOSOPHY / Political; Militär; Whistleblowing; Geheimdokument; USA; Biografie